Penggunaan kaedah "Rawatan Jarak Jauh" dalam rawatan penyakit di pusat rawatan Islam di Malaysia: satu analisis hukum - Ahmad, K.; Ramli, R. (Department of Fiqh and Usul, 2011)

(untitled)
Long distance treatment is one of the methods conducted at the Islamic Treatment Centres in Malaysia. Through this method of treatment, the practitioners are not in the situation of being face-to-face with their patients. In contrast, the treatment will be carried out by using certain approaches and skills without the attendance of the patients’. Therefore, there will be some sorts of doubt and uncertainty in their way of treatment since it will be carried out without any face-to-face meeting with the patients. The question is, to what extent is this way of treatment allowed in Islam? Hence, this article seeks to analyse the views of Muslim scholars pertaining to this method of treating disease. Through field studies conducted at 23 Islamic Treatment Centres throughout Malaysia, data pertaining to the use of the long distance treatment were collected. Data collection was based on interviews and direct observation. The study found that there is only one hadith which can be relied upon concerning the usage of long distance treatment. Basically this method of treatment was allowed by the Prophet SAW. In overall, from the Islamic perspective, the practice of this treatment can be divided into two different views; first: it is permissible but should be based on certain conditions, and second, the method is prohibited.